Essentials of Spring 5.0 for developers - Kennedy, Will; Safari eBooks ([Place of publication not identified] : Packt, 2017)
"With the advent of containerization and the ease of cloud availability, developers are required to explore new tools and frameworks in order to best utilize these technologies. The Spring framework's core features can be used by any Java application, but there are extensions to build web applications on top of the Java EE platform. In this course, you will start by setting up the developer environment, and initialize a simple application using Spring Boot. After that, you will look into different developer tools, debug Spring applications, and log in to Spring. Then you'll dive into the Spring MVC, where you will develop reactive web applications with Spring, and work with embedded servlet containers and manage serialization with Protobuf, Avro, and Thrift.Moving on, we'll look into the various features of Spring Data, and how you can enhance data management using Spring Data JPA, MySQL, REST, NoSQL, and Cassandra. Finally, you will learn to add authentication and security to your web application using Spring security features, such as OAuth2 and JSON Web Token."--Resource description page.
Title from resource description page (viewed June 27, 2017).
Presenter, Will Kennedy.
Keywords: Spring Framework (Computer File); Application program interfaces (Computer software); Aspect-oriented programming; Java (Computer program language); XML (Document markup language); Database design; Electronic books